2006
DOI: 10.1111/j.1468-2478.2006.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion and Foreign Policy: The Stages of Presidential Decision Making

Abstract: Do presidents incorporate the preferences of the public into their foreign policy decisions? Previous scholarship has begun to sketch out the sources of variation in the policy-public opinion linkage, but we still lack a clear understanding of the factors that increase or decrease presidential responsiveness. To better explore the relationship, we conceptualize presidential foreign policy making as a five-stage processFproblem representation, option generation, policy selection, implementation, and policy revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 45 publications
0
26
0
1
Order By: Relevance
“…The public is known to pay little attention to trade policies such as free trade agreements (Knecht and Weatherford 2006;Kono 2008;Milner and Tingley 2011;Scheve and Slaughter 2001). However, protectionism was central to American political discourse during the entire 2016 election campaign.…”
Section: Resultsmentioning
confidence: 99%
“…The public is known to pay little attention to trade policies such as free trade agreements (Knecht and Weatherford 2006;Kono 2008;Milner and Tingley 2011;Scheve and Slaughter 2001). However, protectionism was central to American political discourse during the entire 2016 election campaign.…”
Section: Resultsmentioning
confidence: 99%
“…Works on issue salience (Soroka 2003, Knecht and Weatherford 2006, Oppermann and Viehrig 2009) and on elite consensus (Zaller 1994, Powlick and Katz 1998, Kreps 2010 are of particular importance for explaining the Polish case. However, realist perspectives are also needed, since these focus on the importance of international gains (Morgenthau 1978, Waltz 1979, Rose 1998, Mearsheimer 2001.…”
Section: F Doesermentioning
confidence: 99%
“…By investigating Poland's decision to side with the United States in the invasion of Iraq, this article attempts to further an understanding of the circumstances under which democratic governments ignore the public in foreign policy, particularly in decisions to dispatch armed forces to foreign countries. In recent years, scholarly interest in this issue has increased, and researchers have suggested that factors such as elite consensus (Kreps 2010), external security threats (Weitsman 2004, Davis 2012, and low issue salience (Knecht andWeatherford 2006, Oppermann andViehrig 2009) can increase the willingness of governments to ignore the public in their foreign policy decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…This is, perhaps, the point at which the assumption that "the asymmetry between what leaders know and what the public knows" is a significant modifying factor when considering the role of public preferences in foreign policy arenas. 24 One could frame this as an asymmetry of intellectual training as opposed to simple asymmetry of knowledge. Practically speaking, the third stage involves the realization of the high costs and the low probability of success.…”
Section: Realization Of the Costsmentioning
confidence: 99%